Improving Scaling Performance in Research for Development: Learning from a Realist Evaluation of the Scaling Readiness Approach - Damtew, Elias; Douthwaite, Boru; Schut, M.; Sartas, M.; Leeuwis, C. (Springer, 2023)
Complexity-sensitive decision support approaches (CSDSA) have gained prominence in the research for development (R4D) sector. However, limited attention has been given to critically examining the underlying causal assumptions of CSDSAs and their overall effectiveness in navigating complexity and achieving desired outcomes. Scaling Readiness has emerged as a novel CSDSA that is increasingly applied in R4D programs in low- and middle-income countries to improve the scaling of innovation. This study offers theory-based explanations on the extent to which Scaling Readiness supports evidence-based design, implementation and monitoring of scaling strategies in two R4D interventions. The contribution of Scaling Readiness is influenced by various contextual factors, including pre-existing partnerships and established institutional intervention project and performance management practices. The findings underscore the significance of investing in broader institutional impact culture growth. This includes critical evaluation of how funding, incentive, and performance mechanisms enable or constrain evidence-based decision-making and adaptive management at intervention and organizational level towards achieving Sustainable Development Goals.